Partition Coefficient for Work Life Balance, Motivation and Job Security of Professionals in Higher Education (Technical and Non-Technical ) in National Capital Region of Delhi (International Journal of Scientific Research and Management (IJSRM), 2014)
Higher education to service quality provided in Technical and Non-Technical institutes by professionals in Delhi & NCR Region, The data were collected in two phases. About 400 samples collected from selected professors considered simultaneously. The Gap analysis shows that similar to motivation and job security and larger for work life. The relation of gap score is proportional to Work Life Balance, Motivation and Job Security. The finding for work life balance, motivation, and job security were correlated. The Kp values were more effective for sample size 60-81. The present study shows work life balance was more effective for technical professionals. Tie length vales were shown gradual degrees from professors to assistant professors in all the three factors. Log values will also help for improvement to researchers. In non- technical professionals shows more deviation rather than technical professionals. Technical professionals were nearly constant. This data insight institutes to make their policies.